Desarrollo del Plan Estratégico Operativo en Nivel 3300 - Compañía Minera Atacocha - Julca Pérez, Wilfredo (2017)
This paper summarizes my professional experience in Compañía Minera Atacocha from 2005 to July of 2017, doing it continuously in the areas of productivity, mine services, exploitation and development. In Compañía Minera Atacocha, until the year 2015 the mineral exploitation was carried out from deepening levels 2940 and level 2880, transporting the ore by dumpers of 24 Tn to level 3300 to carry out the lifting. The work carried out involved a lot of losses due to dead times in actual hours of work, use of equipment. At the beginning of 2016, a centralized operation at the 3300 level was rethought, which would meet the same tonnage, develop cruises to the mineralized bodies and exploration zones. This operational strategic plan generates a reduction of costs, the optimization of the equipment of drilling, support, load, labor and also lower costs in transport of mineral.